2023
DOI: 10.1002/jmv.28645
|View full text |Cite
|
Sign up to set email alerts
|

KIR2DL4/HLA‐G polymorphisms were associated with HCV infection susceptibility among Chinese high‐risk population

Abstract: Killer-cell immunoglobulin-like receptors 2DL4 (KIR2DL4) and the human leukocyte antigen class I-G (HLA-G) display vital parts in immune responses against hepatitis C virus (HCV) infection. We select four potentially functional single nucleotide polymorphisms (SNPs) of KIR/HLA to explore the associations between KIR2DL4/ HLA-G genetic variants and HCV infection results. In the present case-control study, a total of 2225 HCV-infected high-risk subjects, including 1778 paid blood donors (PBD) and 447 drug users … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The study by Sakhaee et al found that HLA rs4273729 can serve as a potent predictor for HCV rapid virological response and Sustained Virological Response (SVR) 22 . In our previous studies, we found that the single nucleotide polymorphisms (SNPs) of HLA‐DP and HLA‐DP , KIR2DS4 rs35440472 and HLA‐C rs1130838, as well as KIR2DL4 rs660773 and HLA‐G rs9380142, are also associated with increased susceptibility to HCV infection 23–27 . Therefore, based on the above findings and areas that remain unclear, this study aims to explore the genetic associations of five potential functional SNPs within the KIR3DL2 / HLA‐A and HCV infection.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The study by Sakhaee et al found that HLA rs4273729 can serve as a potent predictor for HCV rapid virological response and Sustained Virological Response (SVR) 22 . In our previous studies, we found that the single nucleotide polymorphisms (SNPs) of HLA‐DP and HLA‐DP , KIR2DS4 rs35440472 and HLA‐C rs1130838, as well as KIR2DL4 rs660773 and HLA‐G rs9380142, are also associated with increased susceptibility to HCV infection 23–27 . Therefore, based on the above findings and areas that remain unclear, this study aims to explore the genetic associations of five potential functional SNPs within the KIR3DL2 / HLA‐A and HCV infection.…”
Section: Introductionmentioning
confidence: 75%
“…22 In our previous studies, we found that the single nucleotide polymorphisms (SNPs) of HLA-DP and HLA-DP, KIR2DS4 rs35440472 and HLA-C rs1130838, as well as KIR2DL4 rs660773 and HLA-G rs9380142, are also associated with increased susceptibility to HCV infection. [23][24][25][26][27] Therefore, based on the above findings and areas that remain unclear, this study aims to explore the genetic associations of five potential functional SNPs within the KIR3DL2/HLA-A and HCV infection. The candidate SNPs in our study including KIR3DL2 rs11672983, KIR3DL2 rs3745902, KIR3DL2 rs1654644, HLA-A rs3869062, and HLA-A rs12202296.…”
Section: Introductionmentioning
confidence: 99%